The Relationship between the Quality of Alms and Happiness in Life - Lidinillah, Aufa; Ansoria Sufi, Madina; Victory Sofia, Vonny (Lafadz Jaya Publisher, 2024)
In general, happiness is the biggest goal that humans want to achieve. Many factors make an individual happy. Previous studies have shown that there is a relationship between prosociality and happiness. Several sources say that religion is one of the factors that makes happiness and that humans' relationship with God is the main factor in achieving happiness. The quality of alms is the level of goodness or badness of a material or non-material gift to someone with only the hope of Allah's blessing. This research is a quantitative study which aims to determine the effect of alms on the happiness of life of the Bekasi Group Alms Community couriers. The research subjects were 51 people according to the population of couriers in the community. The data collection technique in this research used a happiness and alms quality questionnaire. The happiness questionnaire refers to the OHQ (Oxford Happiness Questionaire) from Argyle (2001) and the alms questionnaire to measure the quality of alms refers to the concept from Mu'is (2016). The statistical calculation process uses simple linear regression analysis with the results of the regression equation Ŷ = 18,810+0.672.